2021
DOI: 10.1136/bmjopen-2020-042391
|View full text |Cite
|
Sign up to set email alerts
|

How does general practitioner discontinuity affect healthcare utilisation? An observational cohort study of 2.4 million Norwegians 2007–2017

Abstract: ObjectivesPatients may benefit from continuity of care by a personal physician general practitioner (GP), but there are few studies on consequences of a break in continuity of GP. Investigate how a sudden discontinuity of GP care affects their list patients’ regular GP consultations, out-of-hours consultations and acute hospital admissions, including admissions for ambulatory care sensitive conditions (ACSC).DesignCohort study linking person-level national register data on use of health services and GP affilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A recent study from Norway demonstrated that even short breaks in continuity entailed increases in use of OOH services and admissions for ambulatory care-sensitive conditions. 38 More research is needed on what measures may be undertaken to promote stability of RGPs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Norway demonstrated that even short breaks in continuity entailed increases in use of OOH services and admissions for ambulatory care-sensitive conditions. 38 More research is needed on what measures may be undertaken to promote stability of RGPs.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Previous Norwegian studies focus on continuity with RGPs and have demonstrated that CoC is associated with decreased hospital readmissions 21 and reduced utilization of specialist care. 22 , 23 Despite the known benefits of CoC, we have scarce evidence on CoC for patients with chronic diseases in Norway, a group of patients anticipated to especially benefit from CoC.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings support the importance of these follow-up consultations to parents and children, not only making them feel that the GP acknowledged their disease burden but also strengthening their relationship. Hence, a planned follow-up consultation is an important step in creating an enduring doctor–patient relationship, which is a core principle of general practice that has various positive effects on both patient health and healthcare costs 36–39…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a planned follow-up consultation is an important step in creating an enduring doctor-patient relationship, which is a core principle of general practice that has various positive effects on both patient health and healthcare costs. [36][37][38][39] To the best of our knowledge, there is no other study in which parents and children were interviewed about their expectations and experiences of a GP consultation when the child has chronic GI symptoms. This is important because, in a gatekeeping system such as that in the Netherlands, the GP is the first physician to see a child with chronic GI symptoms and will typically manage most cases without referral to secondary care.…”
Section: Discussionmentioning
confidence: 99%